2014
DOI: 10.1016/j.atherosclerosis.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Serum myeloperoxidase/paraoxonase 1 ratio as potential indicator of dysfunctional high-density lipoprotein and risk stratification in coronary artery disease

Abstract: MPO/PON1 ratio could be a useful marker for secondary prevention of coronary artery disease through modulation of HDL function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 29 publications
5
51
0
Order By: Relevance
“…Therefore, we assessed PON1 arylesterase activity in place of mass or paraoxonase activity in the present study. Previous studies have shown that PON1 enzyme activities are significantly decreased in patients with diabetes or cardiovascular diseases [29,30]. Also, low plasma PON1 activity has been associated with the prevalence of cardiovascular diseases [30e32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assessed PON1 arylesterase activity in place of mass or paraoxonase activity in the present study. Previous studies have shown that PON1 enzyme activities are significantly decreased in patients with diabetes or cardiovascular diseases [29,30]. Also, low plasma PON1 activity has been associated with the prevalence of cardiovascular diseases [30e32].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on a similar patient population also highlighted the importance of this reciprocal inhibition [29] . Furthermore, a recent study showed that serum MPO/PON1 ratio may be a potential indicator of dysfunctional highdensity lipoprotein and risk stratification in coronary artery disease [30] . Therefore, MPO/PON1 ratio was also calculated and we found significantly higher MPO/ PON1 ratio in our dyslipidemic patients compared to controls indicating an increased risk for cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that in CVD patients with normal cholesterol levels the interconnection of HDL-C with PON1 is shifted to an interconnection of HDL-C with MPO, a phenomenon that was not observed in the healthy control group [90]. Furthermore, patients with acute coronary symptoms are characterised by a higher MPO/PON1 ratio vs. the healthy control patients, and this ratio is inversely correlated with the HDL-C particle size [27,69]. The MPO has the potential to oxidise apoA-I, which is the main apoprotein of HDL-C that is responsible for RCT and in this way generate dysfunctional HDL-C [34,75].…”
Section: Paraoxonase 1 Myeloperoxidase and Hdl-cmentioning
confidence: 93%